Green roof irrigation management based on substrate water potential assures water saving without affecting plant physiological performance. Issue 4 (16th May 2022) - Tomasella, Martina; De Nardi, Enrico; Petruzzellis, Francesco; Andri, Sergio; Castello, Miris; Nardini, Andrea
Abstract: Irrigation management in extensive green roofs (EGRs) is crucial in Mediterranean and semi‐arid climates, as it should guarantee efficient water use while ensuring plant survival and vegetation cover. However, benefits of maintaining moderately low substrate water potential (Ψs ) have not been adequately investigated to date. An irrigation control unit based on Ψs thresholds for irrigation (MediWater Safe [MWS]) was compared to a common irrigation timer maintaining Ψs  ⁓ 0 MPa (CTR) in shrub‐vegetated Mediterranean EGR modules. The effect of the different irrigation regimes on substrate temperature, plant water relations (leaf conductance to water vapour, midday water potential and turgor loss point) and root vulnerability to heat stress via electrolyte leakage was tested in four shrub species. Decreasing Ψs thresholds to −0.4 MPa reduced irrigation volumes by 68% in 3 summer months. However, the MWS unit neither influenced plant water status and vegetation cover nor induced physiological acclimation responses. Brief irrigation cycles imposed by MWS in the warmest hours reduced substrate surface temperature by 3°C compared to CTR. Plant water status dynamics and root vulnerability to heat were species specific. Progressive stomatal closure and plant decline occurred only in Ceanothus thyrsiflorus and were associated to high root vulnerability to heat. Mortality occurred only in some Ceanothus plants in the CTR module, where higher Ψs favoured the expansion of Hyperucum x moserianum . The results suggest that selecting proper Ψs thresholds for irrigation could optimize EGR benefits, guaranteeing substantial water savings and proper plant establishment. Moreover, we claim root resistance to heat as a key parameter for plant selection in Mediterranean EGRs.